Versatile aquarium for jellyfish: A rearing system for the biomass production of early life stages in flow-through or closed systems - Ballesteros, Ainara; Siles, Pedro; Jourdan, Eric; Gili, Josep-Maria (Frontiers in Marine Science, 2022)
Interest in the rearing of jellyfish has grown exponentially over recent years due to their indisputable potential in a wide variety of uses and research. Here, we describe the design and operation of an effective modified kreisel aquarium that allows to grow of the early planktonic life stages of jellyfish in both flow-through or closed systems. Thanks to its versatile and innovative approach, the aquarium operates for species with a metagenetic life cycle, and allows the metamorphosis of ephyrae from fertilized eggs for species with a holoplanktonic life cycle, such as Pelagia noctiluca. In addition, its configuration allows the mesh screen to be changed in situ, adjusting the size of the mesh according to the growth of the jellyfish and the size of the prey offered. An accessory, named the polyp plate, suspends the polyps in a downward or sideways position, facilitating prey capture, strobilae formation and release of ephyrae. The improvements of this modified kreisel reduce the time-involvement for staff in maintenance routines, and it is an important contribution to jellyfish husbandry techniques and biomass production. These improvements especially target to the culture of the blooming and stinging P. noctiluca, which has been noted to present a host of challenges to the scientific and aquarist communities.